Restoration from eutrophication in interconnected reservoirs: Using a model approach to assess the propagation of water quality improvements downstream along a cascade system. (March 2022) - Vieira Soares, Laura Melo; Calijuri, Maria do Carmo
Abstract: A coupled hydrodynamic-biogeochemical model was applied to simulate scenarios of classic restoration practices to address eutrophication in a cascade system comprised of six reservoirs along the Tietê River (Brazil) from 2008 to 2016. Each restoration scenario was propagated along the cascade system by using a sequential modelling approach. The simulated scenarios revealed which on-land and in-lake restoration techniques are capable of promoting water quality improvements that are propagated to all downstream reservoirs along the cascade system. The present findings may provide a useful management strategy to develop better restoration practices at a basin catchment scale for other lakes and reservoirs along cascade systems worldwide, especially in highly anthropogenic impacted areas, taking advantage of the propagation of water quality improvements in a downstream direction due to a domino effect triggered by the feedback from one water body to the next in a chain. Highlights: Scenarios of restoration practices were propagated along a reservoir's cascade system. The reduction of phosphorus loads was efficient for restoration at the basin catchment scale. The reduction of phytoplankton biomass was not propagated along the cascade system.